PENGARUH KUALITAS PELAYANAN DAN SUASANA CAFE TERHADAP MINAT BERKUNJUNG KEMBALI DI LABERS COFFE BATAM - Vetrick Nainggolan; rezki alhamdi (JURNAL MENATA, 2026)
The rapid growth of the café industry in Batam has intensified competition, requiring cafés like Labers Coffee to enhance service quality and café atmosphere to encourage repeat visits. However, empirical studies examining the simultaneous effect of both variables at Labers Coffee remain limited.This study aims to analyze the effect of service quality and café atmosphere on revisit intention at Labers Coffee Batam, both partially and simultaneously. Methods A quantitative approach with a causal design was employed. The population comprised all customers who had visited Labers Coffee Batam. A sample of 100 respondents was selected using purposive sampling with criteria aged 17–40 years and had visited at least three times. Data were collected through a 5-point Likert scale questionnaire. Validity and reliability tests were conducted, followed by multiple linear regression analysis, classical assumption tests (normality, multicollinearity, heteroscedasticity), and hypothesis testing (t-test, F-test, and coefficient of determination). Results The results showed that service quality had a positive and significant effect on revisit intention (t-count 4.420, Sig. 0.000), and café atmosphere also had a positive and significant effect (t-count 4.726, Sig. 0.000). Simultaneously, both variables significantly influenced revisit intention (F-count 126.152, Sig. 0.000). The adjusted R² value of 0.722 indicated that 72.2% of revisit intention was explained by service quality and café atmosphere, while the remaining 27.8% was influenced by other factors.Service quality and café atmosphere significantly affect revisit intention at Labers Coffee Batam. Improving staff responsiveness, maintaining cleanliness, and enhancing interior comfort are recommended to strengthen customer loyalty.